Corporate Governance Disclosure in Malaysia - ONG, Wei Jiin (2006)
This research provides evidence on corporate governance disclosure in Malaysia based on a sample of 25 Malaysian public listed companies on the Kuala Lumpur Composite Index (KLCI) in the year 1998 and 2005 that are listed on the Bursa Malaysia. The purpose of this dissertation is to examine whether after the launch of the Malaysian Code on Corporate Governance (HLFC, 2000) following the 1997/98 financial crisis, corporate governance in Malaysia has improved in terms of disclosure information in the companies' annual reports. The major source of data collection for this research is companies' annual reports. The corporate governance information that has been disclosed in the annual reports to the public will be compared between 1998 and 2005. The study confirms that there is a significant improvement by the chosen companies in disclosing the corporate governance items as required in the Malaysian Code on Corporate Governance. However, the dissertation commented that there is still much to be enhanced and more compliance needs to be achieved and improved by the companies.